Implementation of the Murabahah Contract in Agricultural Capital Financing (MURNI): An Islamic Economic Law Analysis at KSPPS Nuri East Java, Pasean Branch, Pamekasan - Uswatun Hasanah; Samheri (Journal of Creative Power and Ambition (JCPA), 2026)
This study examines the implementation of the murabahah contract in the Agricultural Capital Financing (MURNI) product at KSPPS Nuri East Java, Pasean Branch, Pamekasan, and analyzes its conformity with the principles of Islamic Economic Law. This research employed an empirical legal research method using a qualitative approach. Primary data were obtained through interviews with the Sharia Supervisory Board and financing officers, while secondary data were collected from legislation, the Compilation of Islamic Economic Law (KHES), the Fatwa of the National Sharia Council-Indonesian Council of Ulama (DSN-MUI), books, and relevant scientific journals. The findings reveal that the MURNI financing product is specifically designed to provide agricultural capital for farmers through a murabahah contract. The financing mechanism reflects the application of a sale and purchase contract rather than an interest-based lending system, thereby supporting productive economic activities in the agricultural sector. From the perspective of Islamic Economic Law, the implementation of the murabahah contract is generally consistent with the principles of Islamic commercial jurisprudence, particularly regarding the use of a sale-based financing scheme. Nevertheless, ensuring comprehensive sharia compliance requires consistent implementation of the essential elements and conditions of murabahah, including transparency in cost disclosure, agreed profit margins, legal certainty of the transaction object, and effective supervision by the Sharia Supervisory Board. Strengthening these aspects is essential to maintain the integrity of Islamic financing practices and to enhance public confidence in sharia-based agricultural financing.